Clinico-Pathological Profile of Bronchogenic Carcinoma in a Tertiary Care Hospital in Bangladesh - Hassan, Md Quamrul; Ahamad, M Shahab Uddin; Rahman, Md Zillur; Ahmed, Syed; Chowdhury, MA Wahab (Journal of Chittagong Medical College Teachers' Association, 2011)
Key words: bronchogenic carcinoma; transthoracic FNAC; cytopathology DOI: 10.3329/jcmcta.v21i1.7678 Journal of Chittagong Medical College Teachers' Association 2010: 21(1):45-49